2013
DOI: 10.1155/2013/591432
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bone Cement Pulmonary Embolism after Vertebroplasty: Case Report and Literature Review

Abstract: Introduction. Acrylic cement pulmonary embolism is a potentially serious complication following vertebroplasty. Case Report. A 70-year-old male patient was treated with percutaneous vertebroplasty for osteoporotic nontraumatic vertebral collapse of L5-S1. Asymptomatic pulmonary cement embolism was detected on routine postoperative chest radiogram and the patient was treated with enoxaparin, amoxicillin, and dexamethasone. At the followup CT scan no further migration of any cement material was reported; and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Gross specimen of bone cement Due to variable incidence of pulmonary embolism, some studies have recommended routine radiographs within 24 hours of procedure for screening. [4,6,7] Various approaches in the treatment of bone cement embolism have been described, depending on the location of the cement and the severity of symptoms. Options include conservative management with or without anticoagulation, endovascular retrieval, and open-heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gross specimen of bone cement Due to variable incidence of pulmonary embolism, some studies have recommended routine radiographs within 24 hours of procedure for screening. [4,6,7] Various approaches in the treatment of bone cement embolism have been described, depending on the location of the cement and the severity of symptoms. Options include conservative management with or without anticoagulation, endovascular retrieval, and open-heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this case report, we presented an incidental finding of a cement embolism in the pulmonary trunk and both pulmonary arteries following vertebroplasty to emphasize the importance of close monitoring of patients following this procedure. Around 100 cases of cement embolism following vertebroplasty were reported in the literature with the majority being asymptomatic [ 6 ]. Previous studies reported cement extrusion into the venous system during the procedure as the primary cause of cement embolisms [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there are no clear guidelines to screen for asymptomatic pulmonary embolisms, some authors recommend routine chest radiographs following vertebroplasty or kyphoplasty in asymptomatic patients [ 8 , 19 ]. A high-density opacity in a tubular branching pattern, corresponding to pulmonary arterial distribution, is usually suggestive of cement pulmonary embolism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its exact prevalence is unknown, ranging between 2 and 26% according to the selected diagnostic imaging method (4). Considering the frequent paucity of symptoms and the use of protocols that do not include thoracic imaging tests following the procedure, it is believed that these estimates may be undervalued (5,6). The diagnosis usually implies a high clinical suspicion, and in patients with lung cancer, with the multiplicity of respiratory symptoms and the frequent overlap with other lung chronic diseases, it may be even more challenging.…”
Section: Introductionmentioning
confidence: 99%